THE EFFECTIVENESS OF WORD WIZARD GAME IN LEARNING VOCABULARY - Yunia, Anna; Sisbiyanto, Amir; ., Indrawati (ELT Forum: Journal of English Language Teaching, 2018)
This study aimed to investigate the significance difference on the students’ comprehending in learning vocabulary for those were taught by using Word Wizard Game for experimental class and were taught by Direct Translation method for control group. The subject of this study was the eighth grade students of SMPN 1 Ambarawa in the academic year 2016/2017. The instrument used to obtain the data were pre-test, post-test, and questionnaire. However, the writer conducted try out test to check whether the instrument was reliable and valid to be used for pre-test and post-test. The data were gathered and calculated using Ms. Excel and SPSS. The result of this study revealed that Word Wizard game could improve students’ vocabulary mastery by significant improvement of students’ achievement. The result analysis of the quantitative data shows that the mean scores of the experimental group increases from 56.00 to 76.31. The t- test of mean difference was 8,875 and t- table was 2.00. The result concludes that the working hypothesis is accepted. It means that there is a significant difference between students who were taught by using Word Wizard game and those who were taught by using Direct Translation method. In addition, the analysis of the questionnaire shows that students were interested towards Word Wizard game for reading narrative text (mean: 3.25). They recognized that the implementation of the technique for learning narrative text made them enjoy the class (agree: 62.5% and strongly agree: 37.5%). Thus, the analysis reveals that Word Wizard game effective in teaching vocabulary.